Hitam putih polisi dalam mengungkap jaringan narkoba - Al Banjary, Saifulrrochman (Jakarta : PTIK Press [dan] Restu Agung, 2005)
Police discretion related to narcotic and psychotropic drug abuse cases in Indonesia.
Originally presented as the author's thesis (Magister Sains--Universitas Indonesia, 2001) under title: Corak diskresi kepolisian dalam penyidikan tindak pidana narkoba di wilayah Polda Metro Jaya.
Includes bibliographical references (p. 236-241)
Keywords: Drug control -- Indonesia; Police discretion -- Indonesia; Undercover operations -- Indonesia; Narcotics, Control of -- Indonesia; Narcotics and crime -- Indonesia